LASER treatment for women with high‐grade vaginal intraepithelial neoplasia: A propensity‐matched analysis on the efficacy of ablative versus excisional procedures. Issue 9 (14th May 2018) - Bogani, Giorgio; Ditto, Antonino; Martinelli, Fabio; Mosca, Lavinia; Chiappa, Valentina; Rossetti, Diego; Leone Roberti Maggiore, Umberto; Sabatucci, Ilaria; Lorusso, Domenica; Raspagliesi, Francesco
Abstract : Objective: To investigate the long‐term effectiveness of LASER treatment in women affected by high‐grade vaginal intra‐epithelial neoplasia. Methods: Data of consecutive women treated for high‐grade vaginal intra‐epithelial neoplasia were retrieved. Efficacy and long‐term effectiveness of ablative and excisional procedures were tested using a propensity‐matched algorithm. Risk of recurrence over the time was assessed using Kaplan–Meier and Cox models. Results: Overall, 204 patients met the inclusion criteria. LASER ablation and exicision were performed in 169 (82.8%) and 35 (17.2%) patients. A total of 41 (20%) patients developed high‐grade vaginal intraepithelial neoplasia at a median follow‐up of 65 (range, 6–120) months. We observed that only HPV persistence (HR: 2.37 [95%CI:1.03, 5.42]; P  = 0.04) was associated with the risk of recurrence at multivariate analysis. Seven (3.4%) invasive cancers of the lower genital tract were observed in our population. Considering the efficacy of type of procedure (after we applied the propensity‐matched analysis), we observed that type of procedure did not influence persistence of HPV infection (22.8% after excision and 15.7% after ablation; P  = 0.424). Similarly, recurrence (17.1% vs. 18.6%; P  = 1.00) and lower genital tract (2.8% vs. 1.4%; P  = 1.00) rates were similar between groups. Conclusions: Women affected by high‐grade vaginal intra‐epithelial neoplasia are at high risk of recurrence. LASER ablation seems to be equivalent to excision in term of long‐term effectiveness. Lasers Surg. Med. 50:933–939, 2018. © 2018 Wiley Periodicals, Inc.